Economic consequences of a sudden stop of energy imports: The case of natural gas in Germany - Tom Krebs (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
This policy report studies the effects of a sudden stop of natural gas imports from Russia on the German economy. The analysis focuses on the supply-side effects that arise when a gas shortage affects production in the gas-intensive manufacturing sectors, with a corresponding production disruption that propagates along the value chain and through the entire economy. In a baseline scenario, a hypothetical gas embargo implemented in May 2022 leads to a short-run decline in aggregate output between 3.2 percent and 8 percent of GDP. In an alternative scenario, in which Germany can easily replace Russian gas imports by alternative imports, the short-run decline in aggregate output following the embargo is between 1.2 percent and 3 percent of GDP. In addition to the supply-side effects, an embargo causes a reduction in output via the demand-side channel. According to recent simulation studies, the demand-side effects of an energy embargo (coal, oil, natural gas) reduce GDP between 2 percent and 4 percent in the short run. These results underscore the high degree of uncertainty regarding the economic consequences of a sudden stop of Russian gas imports in the short run. Finally, an immediate gas embargo also causes permanent economic damage and has significant social implications. In policy terms, the results show the need for the German government to act as swiftly as possible to ensure independence from Russian energy imports. In addition, Germany's future energy system needs to be more resilient to macroeconomic and geopolitical shocks.
Keywords: D2; E1; Q4; 330; energy; sanctions; network effects